Spermatogonial stem cells share some, but not all, phenotypic and functional characteristics with other stem cells - Kubota, Hiroshi (National Academy of Sciences, 2003)
Spermatogonial stem cells (SSCs) are responsible for maintaining spermatogenesis throughout life in the male by continuous production of daughter cells that differentiate into spermatozoa. However, no unique phenotypic markers to identify SSCs have been described. In this study, the SSC surface phenotype was characterized by using flow cytometric cell sorting in conjunction with a transplantation functional assay for SSCs. Highly enriched stem cell activity was found in the MHC class I (MHC-I)(–)Thy-1(+)c-kit(–) cell fraction of the mouse cryptorchid testis. There was little or no stem cell activity in any other fraction. The antigenic phenotype of the MHC-I(–)Thy-1(+)c-kit(–) SSCs was α6-integrin(+)CD24(+)αvintegrin(–)Sca-1(–)CD34(–). Subsequently, testis side population (SP) cells, which are defined by a Hoechst dye efflux assay, were identified. Their surface phenotype was found to be MHC-I(+)Thy-1(–)Sca-1(+), and the transplantation assay demonstrated that the testis SP and SSCs are distinct populations. In several other tissues, the SP has been shown to contain stem cells, but we found that this characteristic does not define SSCs. The identification of a surface phenotype that allows production of a highly enriched SSC population will facilitate functional and genomic studies and enable further comparison with other stem cells.